90=10b-90

Simple and best practice solution for 90=10b-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=10b-90 equation:


Simplifying
90 = 10b + -90

Reorder the terms:
90 = -90 + 10b

Solving
90 = -90 + 10b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-10b' to each side of the equation.
90 + -10b = -90 + 10b + -10b

Combine like terms: 10b + -10b = 0
90 + -10b = -90 + 0
90 + -10b = -90

Add '-90' to each side of the equation.
90 + -90 + -10b = -90 + -90

Combine like terms: 90 + -90 = 0
0 + -10b = -90 + -90
-10b = -90 + -90

Combine like terms: -90 + -90 = -180
-10b = -180

Divide each side by '-10'.
b = 18

Simplifying
b = 18

See similar equations:

| 2(3x-2)=3(2x+4) | | y=x*(x-1) | | 1+5x=-10 | | 6n-3n= | | 5p+7q=45 | | -3(7v-2)+9v=-2(v+4) | | -19u=17-18u | | x-24=25 | | 3.2k=30 | | 31-4x=7(2n+2) | | -3(3x-2)=-3x+25 | | 2x+3(-7-4x)=14-5x | | -70x^2+36x=-10 | | -13-p=6p+1 | | -5(x+2)=x-2+2(2x+2) | | 3(n-15)+8=11 | | (H^2+4h-4)+(5h^2-8h+2)=6h^2-4h-2 | | 1/4+w=6 | | ax+6=(x+3) | | 2w+2l=l | | -16x^2+8x+190=0 | | 1/4+w=61/3 | | -6(x+2)-11=21+4 | | -3(y+5)=15 | | 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p | | 0.09xX=110.30 | | X+(x-1)=2(x+3) | | 12x-2m= | | 3x4/9= |

Equations solver categories